On computational aspects of discrete Sobolev inner products on the unit circle - Castillo, Kenier [UNESP]; Garza, Lino G.; Marcellán, Francisco (Elsevier, 2013)
In this paper, we show how to compute in O(n2) steps the Fourier coefficients associated with the Gelfand-Levitan approach for discrete Sobolev orthogonal polynomials on the unit circle when the support of the discrete component involving derivatives is located outside the closed unit disk. As a consequence, we deduce the outer relative asymptotics of these polynomials in terms of those associated with the original orthogonality measure. Moreover, we show how to recover the discrete part of our Sobolev inner product. © 2013 Elsevier Inc. All rights reserved.
Keywords: Cholesky decomposition; Computational complexity; Discrete Sobolev inner product; Gelfand-Levitan approach; Outer relative asymptotics; Asymptotics; Computational aspects; Discrete components; Fourier coefficients; Sobolev inner products; Sobolev orthogonal polynomials; Computational methods; Mathematical techniques; Fourier analysis